Neglected dimension of social reconstruction after conflict : Children caught between the ethnic sides - Ajduković, Dean (2004)
Major social events, such as natural disasters, affecting thousands of people, disrupt normal patterns of social functioning causing social chaos and community destabilization, also have consequences on the mental health of people. The term loss of communality is used to describe the massive social and individual trauma in which many socio-cultural support systems necessary for recovery were eliminated. Research shows that declines in social support and social embeddedness explain much of the mental health consequences of disasters. The same and much more is true for the communities affected by war. Social context of destruction and reconstruction of a community affected by war is described based on a series of quantitative and qualitative studies done in the decimated city of Vukovar, Croatia. The focus is on the impact on children of having to live in a community struggling with a number of post-war social and ethnic divisions leading to discrimination.